种凹凸棒土的提纯改性方法 (2019)
本发明公开了种凹凸棒土的提纯改性方法，通过以下步骤进行的：将凹凸棒土原矿粉碎，投入到由硅烷偶联剂550、硅烷偶联剂570、铝酸酯偶联剂SG-Al821、防沉降性铝酸酯ASA等组成的有机活性剂的去离子水中磁力搅拌，浸泡静置后倾析溶液得上层凹凸棒土悬浮液，加入由六偏磷酸钠和羧甲基纤维素组成的活化分散剂中协同超声水热法处理，离心、过滤及干燥得凹凸棒土粉粗品，再输送到充满惰性气体氩气的回转式烘干炉内焙烧，焙烧结束冷却静置至常温再取出便得提纯改性后的凹凸棒土粉。本发明无常规的酸洗废水排放，节能环保，以氩气作为焙烧介质提高了凹凸棒土粉的纯度，并且进步增加了其比表面积，提高了其吸附能力，拓宽其应用领域。 The invention discloses a method of purifying and modifying attapulgite, and the method comprises the following steps: crushing attapulgite raw ore, pouring the attapulgite raw ore into deionized water with an organic active agent comprising silane coupling agent550, silane coupling agent 570, aluminate coupling agent SG-Al821, anti-setting aluminate ASA and the like for magnetic stirring, after soaking and standing, decanting the solution to obtain an upper layer attapulgite suspension, adding the upper layer attapulgite suspension into an activated dispersion agent comprising sodium hexametaphosphate and carboxymethyl cellulose for synergistic ultrasonic hydrothermal method treatment, centrifuging, filtering and d